The Definition of Scientific Consensus and the Shifting Debate on GMO Safety (Sociología y tecnociencia, 2026)
Certain people feel negatively towards foods from genetically modified organisms (GMOs). The scientific community views GMOs more positively due to overwhelming evidence demonstrating no negative effects. The debate has moved from what the science says, to what scientists say about what the science says. By examining other scientific consensuses, one can position the current status of the GMO debate on the timeline between speculation and widespread agreement. A delay exists between a scientific consensus forming and its greater acceptance by doctors, politicians, and the public, and the GMO safety debate is currently in that middle stage.
Keywords: food safety; genetically modified organisms; GMOs; scientific controversy; sociology of science